Pemanfaatan zat aktif fitogenik sebagai modulator fermentasi rumen dan metabolisme pasca rumen pada ternak ruminansia - Syafiradewi Yulianti; U.Hidayat Tanuwiria; Yulianri Rizki Yanza (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Ruminant livestock productivity is substantially influenced by the efficiency of rumen fermentation and post-ruminal nutrient metabolism. The increasing restriction on antibiotic use as growth promoters has driven intensive research into plant-derived bioactive compounds, commonly referred to as phytogenic feed additives (PFAs), as alternative modulators of digestive physiology. This review aims to critically examine the scientific evidence on the role of phytogenic active substances, particularly tannins, saponins, and essential oils, in modulating rumen fermentation processes and post-ruminal metabolic pathways in ruminants. A systematic literature search was conducted using Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Google Scholar, employing keywords such as "rumen metabolism," "post ruminal metabolism," "phytogenic feed additive," "tannin," "saponin," "essential oil," and "ruminant nutrition," with publications limited to 2020-2026. Evidence demonstrates that tannins, through protein precipitation mechanisms, significantly reduce ruminal nitrogen degradation and enhance the flow of rumen undegraded protein (RUP) to the small intestine, thereby improving amino acid absorption efficiency. Saponins selectively modulate rumen microbial populations, particularly suppressing methanogenic archaea and protozoa, resulting in reduced enteric methane emissions by 10-25% alongside improved volatile fatty acid (VFA) profiles. Essential oils composed of phenolic terpenoids disrupt microbial membrane integrity, shifting fermentation patterns toward increased propionate production, which carries direct implications for enhanced energetic efficiency. Collectively, the strategic incorporation of PFAs offers a multidimensional approach to simultaneously reduce environmental methane output, optimise feed energy utilization, and support productive performance in ruminant livestock systems.